Graphene-Based Tunable Wideband Metamaterial Absorber With Polarization Insensitivity and Wide Incident Angle - Wang, Liansheng; Xia, Dongyan; Fu, Quanhong; Ding, Xueyong; Wang, Yuan (Frontiers in Physics, 2020)
A graphene-based tunable wideband metamaterial absorber with polarization insensitivity and wide-incident-angle is presented in this paper. The results show that the absorption is over 90% from 5GHz to 8GHz when the fermi level of graphene is 0.5eV, and the absorption can be tuned by electrically changing the Fermi level of graphene. The mechanism of wideband and tunable absorption is explained by calculating the normalized input impedance and monitoring the surface current. Finally, the results adequately verify that the absorption of metamaterial absorber has the advantages of polarization insensitivity and wide-incident-angle. Thus, it holds great potential application value on many fields such as electromagnetic stealth, electromagnetic shielding, communication and so on.